Improvement of Quality of Lecture by Feedback from Students - Anshuman, Naik; Shashikala, Patel; Brijesh, Mukherjee (International Journal of Innovative Research in Medical Science, 2019)
Introduction: Students must evaluate their teachers by giving feedback to their teachers. Methods: 87 1st MBBS students evaluated their 3 teachers separately before and after self correction by questionnaire. Results: Overall rating of Teachers improved. Conclusion: Feedback should be taken from students to improve the quality of lecture.